Background-associated skin color change in seahorses: genetic bases, evolutionary adaptations and implications for ornamental aquaculture - Yingyi Zhang; Haiyan Yu; Chao Zhang; Qiang Lin; Meng Qu (Reviews in Fish Biology and Fisheries, 2026)

Mechanistic bifurcation and coordination modification in peroxymonosulfate activation by cobalt catalysts - Yan Zhao; Fan Wu; Xiaojiao Chen; Yingyi Wang; Li Hui; Hong Lin (Journal of Environmental Chemical Engineering, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Cooperative strengthening of active sites and charge transport for efficient visible-light photodegradation of tetracycline via N-doped copper phenylacetylide - Zheng Hu; Zihao Guo; Yixun Zheng; Yingyi Chen; Zili Lin; Zhenjun Xiao; Ping Chen; Wenying Lv; Guoguang Liu (Journal of Environmental Chemical Engineering, 2026)

Hydrodynamic Performance Assessment of a Hybrid Wave Energy Converter Array–Floating Breakwater System Under Irregular Waves - Hengming Zhang; Chusen Lin; Chengrong Wang; Xu Huang; Yifeng Yang; Binzhen Zhou; Yingyi Liu; Yuming Yuan (Journal of Marine Science and Engineering, 2026)
A hybrid system combining wave energy converters (WECs) and a floating breakwater presents significant potential for developing commercial-scale wave power operations. The assessment of the hydrodynamic characteristics of a WEC array–floating breakwater system under irregular waves remains in the early stages and requires further investigation. Based on the linear potential theory, a time-domain numerical model is established to evaluate the performance of a hybrid WEC array–floating breakwater system in a target sea area. The interaction between the WECs and the floating breakwater is analyzed. Results show that for the hybrid system with a triangular-baffle-type WEC array under irregular waves, the annual average wave power is 1.16 MW and the annual energy production is 10.16 × 103 MW·h, representing a 241.2% improvement compared with that of the isolated WEC array. The standard deviations of the mooring forces for the hybrid system with the triangular-baffle-type WEC array are reduced by 13.8% in the surge direction and 26.9% in the pitch direction, while increasing by 90.0% in the heave direction. Similar conclusions are obtained for the motion of the floating breakwater. The findings and data reported in this study provide guidance for the engineering application of a hybrid WEC array–floating breakwater system.

Oxidative potential of PM2.5 in Guangzhou, Southern China: Source apportionment and association with airborne bacteria - Yuxin Huang; Senchao Lai; Baoling Liang; Jinpu Zhang; Chenglei Pei; Dachi Hong; Xiaoluan Lin; Zhaokang Ruan; Leitao Sun; Yingyi Zhang (Journal of Environmental Sciences, 2026)

Pathways of Adverse Effect on the Blood-Testis Barrier by Environmental Pollutants - Xicha Lin; Yuanlu Ding; Wei Zheng; Yingyi Yao; Nan Wang; Minjie Li; Liang-Hong Guo (Reviews of Environmental Contamination and Toxicology, 2025)

Developmental exposure to echimidine induces locomotor hyperactivity in zebrafish larvae via inhibiting acetylcholinesterase activity - Tingting Lin; Siyu Chen; Yingyi Ren; Junyu Liang; Zhenghong Zuo; Zhiqiang Luo; Jian Yang; Chengyong He (Journal of Environmental Sciences, 2025)

Mechanistic elucidation and catalyst design of Fe-doped ZnCo2O4 spinels for oxygen vacancy–mediated PMS activation - Xiaoling Lin; Yujia Zhao; Liang Zhang; Yingyi Li; Shangru Zhai; Shuang Shan; Hong Guo; Xianquan Li (Chemical Engineering Journal, 2025)

Genomic insights into the brooding reproduction and climate-driven dynamics of Pocillopora damicornis in the Anthropocene - Jie Li; Yali Liu; Zhixin Zhang; Yu Chen; Jian Zhang; Haiyan Yu; Yingyi Zhang; Cong Liu; Zhuang Shao; David G. Bourne; Meng Qu; Si Zhang; et al. (Science China Life Sciences, 2025)

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Global insights into endophytic bacterial communities of terrestrial plants: Exploring the potential applications of endophytic microbiota in sustainable agriculture - Lukuan Huang; Yingyi Fu; Yaru Liu; Yijie Chen; Tingzhang Wang; Meixia Wang; Xianyong Lin; Ying Feng (Science of The Total Environment, 2024)

Corrigendum to “Spectra-phenology integration for high-resolution, accurate, and scalable mapping of foliar functional traits using time-series Sentinel-2 data” [Remote Sensing of Environment 305 (2024) 114082] - Shuwen Liu; Zhihui Wang; Ziyu Lin; Yingyi Zhao; Zhengbing Yan; Kun Zhang; Marco Visser; Philip A. Townsend; Jin Wu (Remote Sensing of Environment, 2024)

Spectra-phenology integration for high-resolution, accurate, and scalable mapping of foliar functional traits using time-series Sentinel-2 data - Shuwen Liu; Zhihui Wang; Ziyu Lin; Yingyi Zhao; Zhengbing Yan; Kun Zhang; Marco Visser; Philip A. Townsend; Jin Wu (Remote Sensing of Environment, 2024)

Humoral immunosuppression of exposure to polycyclic aromatic hydrocarbons and the roles of oxidative stress and inflammation - Yingyi Dai; Qianyun Deng; Qiaojuan Liu; Lin Zhang; Huiquan Gan; Xinhong Pan; Bing Gu; Lei Tan (Environmental Pollution, 2024)

Strategy for improvement of molecular oxygen activation capacity of PPECu by chlorine doping for water decontamination - Yingyi Chen; Zili Lin; Jinfan Zhang; Yang Liu; Danluo Liang; Daguang Li; Yudan Zhang; Haijin Liu; Ping Chen; Wenying Lv; Guoguang Liu (Journal of Hazardous Materials, 2023)

Simplified synthesis of direct Z-scheme Bi2WO6/PhC2Cu heterojunction that shows enhanced photocatalytic degradation of 2,4,6-TCP: Kinetic study and mechanistic insights - Jinfan Zhang; Zili Lin; Zongshun Yu; Yudan Zhang; Danluo Liang; Yingyi Chen; Yu Chen; Ping Chen; Haijin Liu; Wenying Lv; Guoguang Liu (Journal of Hazardous Materials, 2023)

The underappreciated importance of solar radiation in constraining spring phenology of temperate ecosystems in the Northern and Eastern United States - Yating Gu; Yingyi Zhao; Zhengfei Guo; Lin Meng; Kun Zhang; Jing Wang; Calvin K.F. Lee; Jing Xie; Yantian Wang; Zhengbing Yan; He Zhang; Jin Wu (Remote Sensing of Environment, 2023)

Characterizing atmospheric biological aerosols at a suburban site in Guangzhou, southern China by airborne microbes, proteins and saccharides - Xiaoluan Lin; Chenglei Pei; Ting Liu; Qiuzi Shu; Dachi Hong; Zhuoer Huang; Yingyi Zhang; Senchao Lai (Science of The Total Environment, 2023)

Annual performance and dynamic characteristics of a hybrid wind-wave floating energy system at a localized site in the North Sea - Binzhen Zhou; Zhi Zheng; Jianjian Hu; Chusen Lin; Peng Jin; Lei Wang; Yingyi Liu (Ocean Engineering, 2023)

Cost-effective and accurate monitoring of flowering across multiple tropical tree species over two years with a time series of high-resolution drone imagery and deep learning - Calvin Ka Fai Lee; Guangqin Song; Helene C. Muller-Landau; Shengbiao Wu; S. Joseph Wright; K.C. Cushman; Raquel Fernandes Araujo; Stephanie Bohlman; Yingyi Zhao; Ziyu Lin; Zounachuan Sun; Peter Chuen Yan Cheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The genetic basis of the leafy seadragon’s unique camouflage morphology and avenues for its efficient conservation derived from habitat modeling - Meng Qu; Yingyi Zhang; Zexia Gao; Zhixin Zhang; Yali Liu; Shiming Wan; Xin Wang; Haiyan Yu; Huixian Zhang; Yuhong Liu; Ralf Schneider; Axel Meyer; et al. (Science China Life Sciences, 2023)

Pathways of cadmium fluxes in the root of the hyperaccumulator Celosia argentea Linn. - Pingping Jiang; Yingyi Zheng; Jie Liu; Guo Yu; Fanyu Lin (Environmental Science and Pollution Research, 2022)

Investigation on pseudorabies prevalence in Chinese swine breeding farms in 2013–2016 - Yingyi Liu; Shuo Zhang; Qi Xu; Jiajun Wu; Xinyan Zhai; Shuo Li; Jing Wang; Jianqiang Ni; Lin Yuan; Xiaohui Song; Bolin Zhao; Zhi Zhou; et al. (Tropical Animal Health and Production, 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Zhen’an Yang; Wan Xiong; Yingyi Xu; Lin Jiang; Erxiong Zhu; Wei Zhan; Yixin He; Dan Zhu; Qiuan Zhu; Changhui Peng; Huai Chen (Environmental Monitoring and Assessment, 2016)

Dual Role of Vitamin C Utilization in NO2-Induced Oxidative Stress in Lung Tissues of Mice - Yingyi Zhang; Chunyan Ma; Yuhuan Xiao; Chang Liu; Qiang Xu; Yan Wang; Xin Xu; Lin Hao (Bulletin of Environmental Contamination and Toxicology, 2010)

Salicylic Acid-Involved in Lead Tolerance Associated with the Maintenance of Reducing Conditions in Mice - Qiang Xu; Xin Xu; Yingyi Zhang; Chunyan Ma; Guangzhe Li; Lin Hao (Bulletin of Environmental Contamination and Toxicology, 2009)